The seasonal anomalies in ionosphere over Turkey - Cinar, Ali; Karatay, Secil; Arikan, Feza (IEEE, 2016)
The ionosphere is a region on the Earth's upper atmosphere which extends between 50 km to 1000 km from the ground. It is a layer that consists gases which are ionized by solar radiation. Solar radiation and incident angle of the Sun is important to understand how the Ionosphere affects the radio waves. Total Electron Content (TEC) is one of the important parameters that characterizes Ionosphere and directly related with the Sun's activity. The Ionosphere reflects radio waves and provides communication to distance places in short wave radio communication. In this study, behaviours of the Ionosphere in Turkey are examined for soltice and equinox periods between the years 2009 and 2012 which are one of solar minima and solar maxima periods, respectively by using Symmetric Kullback-Leibler Distance and L2 Norm methods.
Keywords: 13. Climate action; 7. Clean energy